2019
DOI: 10.1021/acsami.8b18781
|View full text |Cite
|
Sign up to set email alerts
|

Helical Assembly of Flavin Mononucleotides on Carbon Nanotubes as Multimodal Near-IR Hg(II)-Selective Probes

Abstract: The development of novel methods to detect mercury is of paramount importance owing to the impact of this metal on human health and the environment. We observed that flavin mononucleotide (FMN) and its helical assembly with a single-walled carbon nanotube (SWNT) selectively bind Hg2+ arising from HgCl2 and MeHgCl. Absorption spectroscopic studies show that FMN preferentially forms a 2:1 rather than a 1:1 complex with Hg2+ at high FMN concentrations. On the basis of the analogy to the thymine–Hg–thymine complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…[128] The formation of a helical ribbon of flavin mononucleotide (FMN) around nanotubes was attributed to the cooperative hydrogen bonding between adjacent flavin moieties under concentric 𝜋-𝜋 interactions with nanotube surfaces. [128] Although the nucleotides have demonstrated certain ability for the structure recognition of SWCNTs in subsequent studies, [129,[158][159][160][161] their efficiencies for dispersion and separation are still limited, compared with the widely used ssDNA and conjugated polymers mentioned above.…”
Section: Biomoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…[128] The formation of a helical ribbon of flavin mononucleotide (FMN) around nanotubes was attributed to the cooperative hydrogen bonding between adjacent flavin moieties under concentric 𝜋-𝜋 interactions with nanotube surfaces. [128] Although the nucleotides have demonstrated certain ability for the structure recognition of SWCNTs in subsequent studies, [129,[158][159][160][161] their efficiencies for dispersion and separation are still limited, compared with the widely used ssDNA and conjugated polymers mentioned above.…”
Section: Biomoleculesmentioning
confidence: 99%
“…[129,363] Paradimitrakopoulos and Ju et al found that FMN containing a chiral D-ribityl phosphate chain with a right-handed helix can wrap around nanotubes in a helical pattern depending on the chirality and handedness of the SWCNTs. [128,129,158,159,364] In addition, Nakashima et al designed and synthesized copolymers composed of PFO and chiral binaphthol moieties for the enantiomer separation of (6, 5) and (7, 5) SWCNTs (Figure 19c). [363] Most recently, Xu et al synthesized an chiral polyfluorene that can be cleaved by acid; this polyfluorene exhibits strong recognition for SWCNT enantiomers through simple bath sonication and centrifugation (Figure 19d).…”
Section: Molecular Wrapping-based Enantiomer Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…e ion-selective electrode (ISE) method, as a rapid analytical tool, has been widely developed in the elds of the environment, medicine, and agriculture due to its advantages of fast speed, simple preparation, low cost, and high sensitivity [11]. In the process of preparing ion-carrier membranes with di erent selective electrodes, many organic, and inorganic complexes can be used as selective carriers of Mercury ions, such as crown ether [12], amide [13], glycidyl diamine [14], metalloporphyrin [15], Schi base [16], calixarene derivatives [17,18], and alkylamine Mercury salt complexes [19]. erefore, there is an urgent need to prepare Mercury ion-selective electrodes with good selectivity and a low detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…Widely applied for the nanotubes sorting flavin mononucleotide (FMN), as is known, can form a dense double-row coating both on some SWCNTs and on planar graphene [31][32][33][34][35][36]. Here, using this experimental fact, we first reduce the geometric conditions for successful formation of the coating (and, therefore, successful sorting of SWCNTs by these molecules) to an analysis of commensurability and geometric characteristics of MPs appearing between layers of a specific virtual bilayer nanotube.…”
Section: Introductionmentioning
confidence: 99%